PSYCHOPHYSIOLOGICAL FEATURES MUSICALLY GIFTED STUDENTS 12-20 YEARS - Lubov Ivanovna Gubareva; Andrey Gorgon'yevich Soloviev; Helen Victorovna Agarkova; Tatyana Nikolaevna Gutko; Kseniya Stanislavovna Beznaeva (Наука. Инновации. Технологии, 2022)
The study involved 38 students of the music school and Music College, has successfully played the piano. The control group consisted of 48 students of secondary school and university, which is not practice music. It was found that in the process of learning to play the piano in a greater degree developed a sense of harmony frets and a sense of altitude sound, working-out and originality creative thinking, especially among boys. This causes a higher occupational success and social adjustment of man-instrumentalist comparatively with women. The method of computer chrono reflexometry proved that the physiological basis of musical talent and creative thinking serve the higher lability and excitability of the central nervous system, a higher level of activation and reliability of its operation.